GlasVent—The Rapidly Deployable Emergency Ventilator. Issue 12 (6th September 2020) - Christou, Adamos; Ntagios, Markellos; Hart, Andrew; Dahiya, Ravinder
Abstract: As a result of the novel Coronavirus disease (COVID‐19) outbreak, a surge is witnessed in the demand for mechanical ventilators needed for treating affected patients. With the rapidly virus spreading around the globe, the shortage of ventilators becomes a global challenge and numerus efforts are followed. While industry mobilizes toward producing medical grade equipment, a number of low‐cost and less complex emergency ventilators have been developed, mainly through academic and open‐source channels, with a hope to meet any temporary needs gap until medical grade ventilator provision becomes sufficient. Herein, the design and implementation of one such emergency ventilator called GlasVent is presented, which an automated version of manual resuscitator device, commonly known as big valve mask or artificial manual breathing unit bag and widely used prior to initiating the mechanical ventilation. GlasVent uses 3D printed mechanical parts, widely available materials and off‐the‐shelf electronic and sensing devices which can be fast assembled. Furthermore, it requires minimal training and can be operated manually by hands or legs, thus meeting the emergency requirements even in the low‐resource settings or regions with less developed healthcare systems. Post‐COVID‐19, such ventilators can potentially find use in clinical care of a wider variety of patients with injury, pulmonary noncommunicable diseases, and severe asthma etc. Abstract : The increase in the demand for ventilators due to rapid spread of novel coronavirus and the resulting pandemic is a global challenge. This paper presents an emergency ventilator called GlasVent, which uses 3D printed parts, widely available materials and off‐the‐shelf electronics and sensing devices. The GlasVent ventilator can be operated automatically or manually by hands or legs.